Interactive Shape Design - Cani, Marie-Paule; Igarashi, Takeo; Wyvill, Geoff (Synthesis Lectures on Computer Graphics and Animation,, 2008)
Providing an intuitive modeling system, which would enable us to communicate about any free-form shape we have in mind at least as quickly as with real-world tools, is one of the main challenges of digital shape design. The user should ideally be able to create, deform, and progressively add details to a shape, without being aware of the underlying mathematical representation nor being tied by any constraint on the geometrical or topological nature of the model. This book presents the field of interactive shape design from this perspective. Since interactively creating a shape builds on the humans ability of modeling by gesture, we note that the recent advances in interactive shape design can be classified as those that rely on sculpting as opposed to sketching metaphors. Our synthetic presentation of these strategies enables us to compare the different families of solutions, discuss open issues, and identify directions for future research. Table of Contents: Introduction / Sculpting Metaphors / Sketching Systems / Future Directions: Modeling by Gesture.